System to Evaluate the Skill of Operating Hydraulic Excavators Using a Remote Controlled Excavator and Virtual Reality - Sekizuka, Ryota; Ito, Masaru; Saiki, Seiji; Yamazaki, Yoichiro; Kurita, Yuichi (Frontiers in Robotics and AI, 2020)
We developed a system to evaluate the skill of operating a hydraulic excavator. The system employs a remotely controlled (RC) excavator and virtual reality (VR) technology. We remodeled the RC excavator so that it can be operated in the same manner as a real excavator and proceeded to measure the excavator's state. To evaluate the skill of operating this system, we calculated several indices from the data recorded during excavation work and compared the indices obtained for expert and non-expert operators. The results revealed that it is possible to distinguish whether an expert or non-expert is operating the RC excavator. We calculated the same indices from the data recorded during excavation with a real excavator and verified that there exists a high correlation between the indices of the RC excavator and those of the real excavator. Thus, we confirmed that the indices of the real excavator and those of the simulator exhibited similar trends. This suggests that it is possible to partly evaluate the operation characteristics of a real excavator by using an RC excavator with different dynamics compared with a real excavator.